Anthelmintic acetogenin from Annona squamosa L. Seeds - Souza,Marta M.C. (2008)
Annona squamosa seeds extracts showed anthelmintic activity against Haemonchus contortus, the main nematode of sheep and goat in Northeastern Brazil. A compound 1 was isolated from ethyl acetate extract and inhibited the egg hatching of H. contortus at 25 mg ml-1. The structure of 1 was determined as a C37 trihydroxy adjacent bistetrahydrofuran acetogenin based on spectroscopic analysis.